Golos iz khora - Terts, Abram, 1925-1997. (London : Stenvalley Press, 1973)
Compiled almost exclusively from author's letters to his wife from Soviet concentration camps, 1966-1971. Contains snippets of literary thoughts as well as the comments and conversations of fellow prisoners, most of them criminals or even German war prisoners.
Afterword signed: Igorʹ Golomshtok.
HU OSA 300 - RFE/RL collection
Samizdat and Emigré Publications
Keywords: Authors, Russian; Dissenters -- Soviet Union; Political persecution -- Soviet Union